We should concern about Nipah virus epidemic in Bangladesh - Roney, Miah (Springer Nature, 2024)
The zoonotic Nipah virus (NiV) is very lethal and may spread from animals to people. There is yet no known cure or therapy for NiV. The outbreaks are seasonal in Bangladesh, occurring between December and April, with cases reported almost annually. Since the virus was discovered in Bangladesh in 2001, 341 individuals had been affected, and as of February 2024, 242 fatalities have been documented. The case fatality rate (CFR) for NiV has been estimated to range from 40 to 75% in Bangladesh according to the World Health Organisation (WHO). As a result of the high CFR, difficulties in diagnosing the virus, and lack of specific treatments or vaccines for NiV infection, the WHO rates the overall risk at the national level as moderate. The virus has the potential to become a global public health concern due to its ability to spread from individual to person and beyond the region.